Profiling the dysregulated immune response in sepsis: overcoming challenges to achieve the goal of precision medicine - Cajander, Sara; Kox, Matthijs; Scicluna, Brendon P; Weigand, Markus A.; Mora, Raquel Almansa; Flohé, Stefanie B.; Martin-Loeches, Ignacio; Lachmann, Gunnar; Girardis, Massimo; Garcia-Salido, Alberto; Brunkhorst, Frank Martin; Bauer, Michael; et al. (The lancet. Respiratory medicine, 2023)
Sepsis is characterised by a dysregulated host immune response to infection. Despite recognition of its significance, immune status monitoring is not implemented in clinical practice due in part to the current absence of direct therapeutic implications. Technological advances in immunological profiling could enhance our understanding of immune dysregulation and facilitate integration into clinical practice. In this Review, we provide an overview of the current state of immune profiling in sepsis, including its use, current challenges, and opportunities for progress. We highlight the important role of immunological biomarkers in facilitating predictive enrichment in current and future treatment scenarios. We propose that multiple immune and non-immune-related parameters, including clinical and microbiological data, be integrated into diagnostic and predictive combitypes, with the aid of machine learning and artificial intelligence techniques. These combitypes could form the basis of workable algorithms to guide clinical decisions that make precision medicine in sepsis a reality and improve patient outcomes.